How to transform cultivated land protection on the Northeast Tibetan Plateau？ A multifunctional path exploration - Rongrong Ma; Yuhan Huang; Wei Zhou; Jun Ren; Hongyu Wang; Zeyu Shi; Juan Wang (Ecological Indicators)
The coordinated development of ecological services, food production, and human survival presents new challenges for protecting cultivated land (CL) in the ecologically fragile region of the Tibetan Plateau (TPEFR). There is an urgent need to explore transformative pathways for conserving CL in the region. In this study, a multifunctional supply and demand perspective is taken to explore such pathways. Correlation analysis and a coupled coordination degree model are used to understand the intrinsic structural characteristics that impact the multifunctionality of CLs. The K-means clustering algorithm is utilized to identify the alignment between the supply and demand of multiple CL functions and determine dominant and deficient CL functions. Finally, a comprehensive zoning approach is employed to enhance the dominant functions of CL, and transformation zones and the corresponding directions of these functions are identified, along with proposed countermeasures. The findings indicate the following: (1) There were disparities between the supply and demand of production, life, and ecological functions in Qinghai Province from 2000 to 2020. (2) A trade-off relationship exists between the supply and demand of CL production and ecological functions. (3) The degree of coordination between CL functions decreases from east to west in Qinghai Province. (4) CL resources in Qinghai Province can be categorized into eight zones. Among these, four zones undergo function-enhancing transformation to enhance production function, life function, ecological function, and multifunctional synergistic enhancement and protection. The remaining four zones prioritize the protection of ecological functions. In this study, a new paradigm is provided for the protection of CL in the TPEFR. The intrinsic mechanism and extrinsic aggregation of multifunctional supply–demand relationships are considered for comprehensive multifunctional zoning of CL, and the different transformation areas and their transformation directions are clarified.